2020
DOI: 10.1080/13602381.2020.1779496
|View full text |Cite
|
Sign up to set email alerts
|

The role of leadership in human resource management: perspectives and evidence from Asia Pacific

Abstract: The objective of this special issue is to advance our understanding of the role of leadership at all levels of organizational hierarchies in promoting effective human resource management (HRM) in the broadly defined Asia Pacific region. Leadership and HRM are two key factors affecting outcomes at organizational, team/unit, and individual levels either within the same country or in a cross-border context (Boada-Cuerva, Trullen, and Valverde 2019; Chang 2016; McClean and Collins 2019; Steffensen et al. 2019). Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
2
15
0
1
Order By: Relevance
“…Previous studies found that HRM correlated with leadership (Gill et al, 2018;Lopez-Cabrales et al, 2017;Zhao et al, 2020), but studies on future HRM (analytical skills, employment relations and future workspace) and self-leadership could not be found. Suan and Nasurdin (2014), Aybas and Acar (2017), Alzyoud (2018), Guan and Frenkel (2018), Ahmed et al (2019) and Tensay and Singh (2020) found that HRM had a positive relationship with work engagement, but this study found that future HRM had a positive relationship with work engagement.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Previous studies found that HRM correlated with leadership (Gill et al, 2018;Lopez-Cabrales et al, 2017;Zhao et al, 2020), but studies on future HRM (analytical skills, employment relations and future workspace) and self-leadership could not be found. Suan and Nasurdin (2014), Aybas and Acar (2017), Alzyoud (2018), Guan and Frenkel (2018), Ahmed et al (2019) and Tensay and Singh (2020) found that HRM had a positive relationship with work engagement, but this study found that future HRM had a positive relationship with work engagement.…”
Section: Discussionmentioning
confidence: 77%
“…Human resource management practices (high performance, high commitment, high control, high involvement and international HRM) and leadership (authentic, ethical, transformative, paternalistic, authoritarian and global leadership, and leader-member exchange) have interactive effects on organisational, team/unit and individual outcomes (Zhao, Liu, Zhu, & Liu, 2020). Leadership has an indirect effect on outcomes through HRM practices, and HRM practices may have an indirect effect on outcomes through leadership.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Leadership is defined from a social and political perspective as the role of politicians and managers, with the competency to promote stability within an organization by adapting to the external environment [24]. Theories related to leadership assert that the organization members are more motivated when the leader accepts more challenging roles for its members and takes more enthusiastic action to strive toward achieving the given goals [25,26].…”
Section: Deductive Theory Buildingmentioning
confidence: 99%
“…Markoulli et al 2017), reviews of I/CHRM research (e.g. Sanders and De Cieri 2021), and reviews of issues such as leadership in the Asia-Pacific (Zhao et al 2020), to date we lack a review of the international and comparative HRM research in the Asia-Pacific region. We argue that such a review is important to build understanding of the cross-national and comparative HRM issues that are specific to this region.…”
Section: Our Contributionmentioning
confidence: 99%
“…This scholarship has tended to overlook important contextual factors such as institutional factors and societal norms that require understanding of the local contexts in Asia-Pacific countries (Bhagat, McDevitt and McDevitt 2010). There is emerging evidence that, possibly as a consequence of incomplete information, management and HRM practices developed in Western contexts may not fulfil their intended purpose when transferred into Asia-Pacific contexts (Zhao et al 2020).…”
Section: Introductionmentioning
confidence: 99%